Neuroprotective Mechanisms of PPARδ: Modulation of Oxidative Stress and Inflammatory Processes - Schnegg, Caroline I. (Hindawi Publishing Corporation, 2011)
Peroxisome proliferator-activated receptors (PPARα, δ, and γ) are ligand-activated transcription factors that regulate a wide range of cellular processes, including inflammation, proliferation, differentiation, metabolism, and energy homeostasis. All three PPAR subtypes have been identified in the central nervous system (CNS) of rodents. While PPARα and PPARγ are expressed in more restricted areas of the CNS, PPARδ is ubiquitously expressed and is the predominant subtype. Although data regarding PPARδ are limited, studies have demonstrated that administration of PPARδ agonists confers neuroprotection following various acute and chronic injuries to the CNS, such as stroke, multiple sclerosis, and Alzheimer's disease. The antioxidant and anti-inflammatory properties of PPARδ agonists are thought to underly their neuroprotective efficacy. This review will focus on the putative neuroprotective benefits of therapeutically targeting PPARδ in the CNS, and specifically, highlight the antioxidant and anti-inflammatory functions of PPARδ agonists.